Improving Students Activity and Students Learning Outcomes by Using Possing Problem Model - Slamet Widiono (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
The purpose of the research to describe the using of Possing Problem for increasing the students’ activities and the students learning outcomes, to know the using of Possing Problem can increase students activities, and to know the using of Possing Problem can increase students learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIII at SMP Islam Terpadu Syarif Hidayatullah. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and mathematical student learning outcomes.Keywords: Possing Problem, students activity, and learning outcomes